Soil P availability and mycorrhizal type determine root exudation in sub-tropical forests. (August 2022) - Jiang, Zheng; Thakur, Madhav P.; Liu, Ruiqiang; Zhou, Guiyao; Zhou, Lingyan; Fu, Yuling; Zhang, Peipei; He, Yanghui; Shao, Junjiong; Gao, Jing; Li, Nan; Wang, Xinxin; et al.
Abstract: Root exudates determine plant's ability to acquire nutrients through influencing plant's interactions with soil microorganisms. Recent studies suggest that plant's associations with beneficial soil microorganisms explain variation in root exudation as plants opt to minimize the exudation cost through such symbiosis. Yet, we have a poor understanding of whether plants change their exudation rates through mycorrhizal symbiosis in soil environments with varying resource availability. Here, we report the effects of plant-mycorrhizal symbiosis on root exudation rates across a gradient of soil phosphorous (P) availability from a field experiment in subtropical forests. Root exudation rates were higher in plants partnering with arbuscular mycorrhizal fungi than those with ectomycorrhizal fungi, but this difference disappeared in soils with high P. Specific root surface area, specific root length and fine root vitality explained high root exudation in P-limited soils. These findings demonstrate that mycorrhizal symbiosis and root functional traits collectively determine the variation in root exudation in P-limited environments. Highlights: Root exudation rates were greater in AM trees than in ECM trees. Root exudation rate decreased with soil P availability in sub-tropical forests. Root morphology and vitality were the main drivers of root exudation rates.